Factors Related to Attitudes Toward the COVID-19 Vaccine and Perception of Control of COVID-19 of Healthcare Workers in Turkey - Arpacıoğlu, Selim; Yalçın, Murat; Saral, Ertuğrul; Çakıroğlu, Oya (Cerrahpaşa Medical Journal, 2022)
Objective: This study aims to investigate the sociodemographic, occupational, and psychological factors related to attitudes toward the COVID-19 vaccine and perception of control of COVID-19 among the healthcare workers in Turkey. Methods: This study has a descriptive and cross-sectional design, and 813 healthcare workers were included using the convenience and snowball sampling methods. The data were collected via online survey. Patient Health Questionnaire (PHQ-4), The Perception of Control of COVID-19 Scale (PCo-COVID-19) which has 3 subscales as macro-control, micro-control, and controllability, and Attitudes Toward the COVID-19 Vaccine (ATVCOVID- 19) which has 2 subscales (positive and negative attitude) were used as data collection tools. Results: The healthcare workers scored 1.93 ± 1.56 and 2.39 ± 1.63, respectively, in the anxiety and depression subscales of PHQ-4. The total scores obtained from PCo-COVID-19 and ATV-COVID-19 Vaccine Scale were 2.70 ± 0.56 and 3.56 ± 0.77, respectively. Our results indicated a very weak negative correlation between the anxiety and depression levels of healthcare workers and ATV-COVID-19 positive attitudes subscale scores. In addition, there was a negative relationship between the macro-control and controllability subscales, and a negative relationship with the micro-control subscale of ATV-COVID-19 and PCo-COVID-19. In multiple linear regression analysis, the variables of age, occupation, macro-control, micro-control, and controllability were found to be related to positive attitude subscale of ATV-COVID-19 scores. Conclusion: The attitudes toward the vaccine of the healthcare workers were positive, while their beliefs regarding the controllability of COVID-19 pandemic were negative. Increase in anxiety and depression levels was found to be a risk factor for decreased positive attitude toward the COVID-19 vaccine. Finally, the attitude toward the COVID-19 vaccine was better among the healthcare workers who highly believed in the effectiveness of national and global measures, rather than individual ones. Cite this article as: Arpacıoğlu S, Yalçın M, Saral E, Çakıroğlu O. Factors related to attitudes toward the COVID-19 vaccine and perception of control of COVID-19 of healthcare workers in Turkey. Cerrahpaşa Med J. 2022;46(3):249-257.